Regeneration of the inhalant siphon of mesodesma mactroides (Deshayes, 1854) (Mollusca: Bivalvia) - Nuñez, Jesus Dario (2010)
Infaunal biota faces the compromise between predation avoidance and contact with the surface to maintain such biological functions as feeding, excretion, respiration, and reproduction. In this study, we conducted the regeneration process of artificially cropped inhalant siphon of M. mactroides at different seasons and levels of artificial severing to establish regeneration time in each condition.The regeneration process started a day after the ablation of the distal end of the inhalant siphon, when the primary tentacles initiate their development. The most dramatic events in the regenerating process of the inhalant siphon were detected within the first 96 hours after the treatment, with fast regeneration of primary and secondary tentacles, whereas the regeneration of tertiary tentacles delayed until the twelfth day in winter and eighth day in spring. Therefore, primary and secondary tentacles must play a more important role in providing basic functionality to the siphon. The slow process of regeneration observed within the first day after ablation of the tentacle crown occurs probably due to the malfunctioning of the siphon addition the physiological adequation needed for the tissue reparation, therefore limiting the food and oxygen intake of individuals with removed tips. In this study was observed that individuals belonging to the same clam population increased the regeneration rate from winter to spring. It is still to be tested if these rate influences in the time that the clams remain exposed predators.